In silico dynamic molecular interaction networks for the discovery of new therapeutic targets - Vujasinovic, T.; Zampera, A. S.; Jackers, P.; Sanoudou, D.; Depaulis, A. (Curr Pharm DesCurr Pharm DesCurr Pharm Des, 2010)
Systems biology has emerged as a major trend in biological research during the past decade. As living organisms are described in more and more detail, it aims at filling the gap between understanding basic molecular processes and complex biological systems in which new properties often emerge from the combination of these elementary processes. This approach culminates in the development of computer-based mathematical models of physiological and pathophysiological processes. We review the state of the art in dynamic modelling, with emphasis on two complementary approaches: the modelling of small systems that is mostly developed by academic teams and aims at understanding generic biological properties, and the modelling of large systems that is mostly implemented by industrial companies and aims at the generation of new therapeutic strategies. We also provide an example of such large-scale modelling applied to the identification of drug targets for neurodegeneration.
Keywords: *Models, Biological; Brain Diseases/*drug therapy/genetics; Computational Biology/*methods; computer simulation; Drug Therapy/*methods; gene expression profiling; Humans; Molecular Targeted Therapy; Mutation/drug effects; Pharmacogenetics/*methods; Polymorphism, Genetic/drug effects; Precision Medicine/*methods; Proteomics